2008
DOI: 10.1002/aoc.1432
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐catalysed Suzuki cross‐coupling of primary alkylboronic acids with alkenyl halides

Abstract: The Suzuki reaction of primary alkylboronic acids with alkenyl halides proceeds nicely using the air-stable catalyst PdCl(C 3 H 5 )(dppb), Cs 2 CO 3 as base and toluene or xylene as solvent. A minor effect of the substituent position of the alkenyl bromide was observed. Quite similar yields were observed in the presence of α-or β-substituted alkenyl bromides such as 2-bromobut-1-ene or 1-bromo-2-methylprop-1-ene with this catalyst. This reaction proceeded with a variety of alkylboronic acids such as 2-phenylet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Current methods for the synthesis of 2‐alkenes (Scheme a), such as Wittig olefination and alkene isomerization, suffer from low Z / E selectivity. In addition, cross‐coupling reactions require a preinstalled Z ‐alkenyl bromide . Semi‐hydrogenation of 2‐alkynes is the most reliable method to achieve excellent control of Z selectivity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current methods for the synthesis of 2‐alkenes (Scheme a), such as Wittig olefination and alkene isomerization, suffer from low Z / E selectivity. In addition, cross‐coupling reactions require a preinstalled Z ‐alkenyl bromide . Semi‐hydrogenation of 2‐alkynes is the most reliable method to achieve excellent control of Z selectivity.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, crosscoupling reactions require a preinstalled Z-alkenyl bromide. [7] Semi-hydrogenation of 2-alkynes is the most reliable method to achieve excellent control of Z selectivity. However, the preparation of 2-alkynes from terminal alkynes relies on the use of sensitive organometallic reagents and highly toxic methyl iodide.…”
mentioning
confidence: 99%
“…[26] More recently, Doucet demonstrated that the PdA C H T U N G T R E N N U N G (OAc) 2 -catalyzed reaction of methyl (E)-3-(furan-3-yl)acrylate (39) with (hetero)aryl bromides under ligand-free conditions in DMA at 130 8C in the presence of KOAc as the base occurred selectively at C-2 to give compounds 40 in low to good yields (Table 1, entries [1][2][3][4][5][6][7][8][9][10][11]. [27] He also found that compounds 40e (entry 5, Table 1) and 40k (entry 11, Table 1) could not be obtained using 0.1 mol% PdA C H T U N G T R E N N U N G (OAc) 2 as the catalyst, but could be prepared in 16 and 58% yield,s respectively, by performing the arylation reactions at 150 8C in the presence of 2 mol% [35,40] as the catalyst. [27] Nevertheless, the PdCl-…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%
“…[40] In 2012, the first examples of Pd-catalyzed direct C-5 arylation of furans with bromopyridines substituted with an acetyl or a cyano group were described by Bensaid and Doucet. [28] They reported that furans 6 and 8 (2 equiv.)…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%
“…[5,6] Reactions of alkenyl halides with alkyltrifluoroborates with PdCl 2 (dppf)·CH 2 Cl 2 as catalyst and Cs 2 CO 3 as base have proceeded in a similar way. [9] Over the last few years, as benzyl, phenyl, allyl, and alkyl are tolerated at the 1-and 3-positions of the 2-bromoalken-3-ols. [8] Recently, Santelli and co-workers reported the coupling of alkenyl bromides and chlorides with primary alkylboronic acids by using PdCl(C 3 H 5 )(dppb) as catalyst and expensive Cs 2 CO 3 as base, affording the coupling products in moderate yields (40-71 %).…”
Section: Introductionmentioning
confidence: 99%